The right of compensation to the HIV victim in Malaysia: an analysis from the case of Abd Rahim bin Abd Rahman v public prosecutor - Mohamed, Mazita; Hashim, Marina; Abdul Rahim, Asmar (Global Academic Excellence, 2018)
In a criminal trial, the stature of the victim is only limited to being a witness or purveyor of evidence. Issues concerning the victim of a crime normally concern the punishment of criminals. Inevitably, the victim’s interest as the aggrieved party has not been properly taken care of. For instance, the court in seeking justice would award the appropriate punishments or sentences to the accused whilst neglecting or overlooking the aspect of ‘curing’ or ‘relieving’ the victim’s pain and suffering from the criminal act. In relation to HIV transmission in sexual offences, one may suffer a lifetime ‘pain’ mentally, physically and emotionally. In addition, economically one would further have to bear medical costs and expenses. Thus, the court in carrying out justice may both compensate the victim and punish the offender simultaneously. In line with the above scenario, this paper seeks to analyse the case of Abd Rahim Bin Abd Rahaman v Public Prosecutor with regard to the Court’s effort in affirming the seriousness of the HIV transmission in sexual offences. The finding shows that section 426 of the Criminal Procedure Code allows the court to make an order for the payment of compensation to the victims subject to the application made by the Public Prosecutor. The case of Abd Rahim however did not discuss the issue of compensation in depth. As a concluding suggestion, the Public Prosecutor in assisting the Court to delivering justice should also address the issue of compensating the victim by invoking section 426 of the Criminal Procedure Code (Act 593).